L. W. Moultrie, Charter and Ordinances of the City of Fresno 30, § 8 (1896) - (:unkn) unknown (My University, 1896)
Prohibited the concealed carrying of any pistol or firearm, slungshot, dirk, Bowie knife, or other deadly weapon, absent written permission.
Keywords: CARRY - CONCEALED